ASSESSMENT OF SMALLHOLDER FARMERS’ VULNERABILITY TO CLIMATE CHANGE IN OGUN STATE, NIGERIA - Fatoki O.A.; Adesope A.A.; Awe F.; Oguntoye T.O.; Arowolo O.V. (Russian Journal of Agricultural and Socio-Economic Sciences, 2020)
This study investigated the assessment of smallholder farmers’ vulnerability to climate change in Ogun State, Nigeria. A multi-stage sampling technique was used to select 150 farmers in the agricultural zones of Abeokuta, Ijebu and Ilaro. Data were collected with the aid of well structured questionnaire from the farmers. Descriptive statistics and Principal Component Analysis (PCA) were used for the data analyzed. The average age of the respondents was 45.5 years. The majority were married with an average household size of 5 persons while a larger percentage of the respondents are involved in crop farming. The result shows that most of the farmers are aware of variations in the prevailing weather conditions of their area and floods were mostly experienced in the year 2018 and 2019. The vulnerability indices in Ilaro, Abeokuta and ijebu ode agricultural zones were -0.652, 0.250, and 0.303 respectively. This means that Ijebu ode was the least vulnerable to climate change followed by Abeokuta while Ilaro is the most vulnerable. Therefore, the study recommends that an integrated rural development scheme aimed at increasing access to social amenities should be established by the government to strengthen the resilience of rural farmers to climate change.